2018
DOI: 10.1021/acsphotonics.7b01439
|View full text |Cite
|
Sign up to set email alerts
|

Highly Broadband Absorber Using Plasmonic Titanium Carbide (MXene)

Abstract: Control of light transmission and reflection through nanostructured materials has led to demonstration of metamaterial absorbers that have augmented the performance of energy harvesting applications of several optoelectronic and nanophotonic systems. Here, for the first time, a broadband plasmonic metamaterial absorber is fabricated using two-dimensional titanium carbide (Ti 3 C 2 T x ) MXene. Arrays of nanodisks made of Ti 3 C 2 T x exhibit strong localized surface plasmon resonances at near-infrared frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
226
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(249 citation statements)
references
References 66 publications
4
226
0
Order By: Relevance
“…To probe only the change in optical properties of the WE, a 0.5 cm diameter hole was made in the Ti 3 C 2 T x CE to avoid contribution of the CE in the UV-vis-NIR spectrum (Figure 1a). [28] According to previous studies, it was suggested that the absorption peak at ≈770 nm corresponds to a plasmonic effect, [42,43] more specifically to a transversal surface plasmon, which would explain the independence of the peak position on the flake size. [28] According to previous studies, it was suggested that the absorption peak at ≈770 nm corresponds to a plasmonic effect, [42,43] more specifically to a transversal surface plasmon, which would explain the independence of the peak position on the flake size.…”
Section: In Situ Electrochemical and Optical Characterization Of Ti 3mentioning
confidence: 96%
See 1 more Smart Citation
“…To probe only the change in optical properties of the WE, a 0.5 cm diameter hole was made in the Ti 3 C 2 T x CE to avoid contribution of the CE in the UV-vis-NIR spectrum (Figure 1a). [28] According to previous studies, it was suggested that the absorption peak at ≈770 nm corresponds to a plasmonic effect, [42,43] more specifically to a transversal surface plasmon, which would explain the independence of the peak position on the flake size. [28] According to previous studies, it was suggested that the absorption peak at ≈770 nm corresponds to a plasmonic effect, [42,43] more specifically to a transversal surface plasmon, which would explain the independence of the peak position on the flake size.…”
Section: In Situ Electrochemical and Optical Characterization Of Ti 3mentioning
confidence: 96%
“…The UV-vis-NIR spectrum of a Ti 3 C 2 T x MXene thin film has several characteristic features, such as a broad absorption peak around 760-780 nm and an absorption peak in the UV region ( Figure 1c). [28] According to previous studies, it was suggested that the absorption peak at ≈770 nm corresponds to a plasmonic effect, [42,43] more specifically to a transversal surface plasmon, which would explain the independence of the peak position on the flake size. [22,43] Electrochromic properties of the Ti 3 C 2 T x device were studied by in situ UV-vis-NIR spectroscopy during electrochemical cycling in 1 m phosphoric acid polyvinyl alcohol gel electrolyte (H 3 PO 4 /PVA gel).…”
Section: In Situ Electrochemical and Optical Characterization Of Ti 3mentioning
confidence: 99%
“…Femtosecond bulk laser has been realized by using few‐layer Ti 3 C 2 T x as saturable absorber . The utilization for plasmonic of MXene has also been demonstrated by Chaudhuri et al Although there have been several important works on the study of MXene in nonlinear optics, the study of the nonlinear optical phenomenon of MXene is still at its early stage, especially the Kerr effect of the MXene and its application have barely been studied. It is intriguing to explore the nonlinear Kerr effect of MXene and investigate its application in the all‐optical signal processing.…”
Section: Introductionmentioning
confidence: 99%
“…Figure d and Figure S7d of the Supporting Information represent the simulated electric‐field ( E ‐field) profiles (| E |/| E 0 |) of different‐generation MXene structures at three NIR wavelengths of 1500, 2000, and 2500 nm. Compared with G 0 MXene structure, the electric field maps of higher generation MXene structures show widely spread hot spots around the MXene structures, indicating field confinement induced by strong localized surface plasmon resonances at near‐infrared frequencies . Through the theoretical and experimental analysis, the broadband light absorption can be concluded as follows.…”
Section: Resultsmentioning
confidence: 96%
“…The thicknesses of G 0 , G 1 , and G 2 MXene nanocoatings were set as same as those of the corresponding experimental samples with the MXene loadings at 0.32 mg cm −2 (i.e., 1140, 284, and 71 nm for G 0 , G 1 , and G 2 MXene nanocoatings, respectively). The permittivity of MXene were referred to the previous work …”
Section: Methodsmentioning
confidence: 99%